2018
DOI: 10.1002/dmrr.3102
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid stimulates the release of insulin and of GLP‐1 in the rat perfused pancreas and intestine

Abstract: Aims Previous results indicate that nanomolar concentrations of abscisic acid (ABA) stimulate insulin release from β‐pancreatic cells in vitro and that oral ABA at 50 mg/kg increases plasma GLP‐1 in the fasted rat. The aim of this study was to test the effect of ABA on the perfused rat pancreas and intestine, to verify the insulin‐ and incretin‐releasing actions of ABA in controlled physiological models. Materials and methods Rat pancreas and small intestine were perfused with solutions containing ABA at high‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Starting from the observation that cADPR was involved in the Ca 2+ signaling leading to insulin release, the effect of ABA on β-pancreatic cells was explored. Indeed, micromolar ABA stimulated insulin release in vitro, from rat insulinoma cells and from isolated human islets [ 12 ], and also in vivo, in the perfused rat pancreas [ 13 ]. In the in vitro study, the role of cADPR as the second messenger of ABA was confirmed, similarly to what observed on innate immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the observation that cADPR was involved in the Ca 2+ signaling leading to insulin release, the effect of ABA on β-pancreatic cells was explored. Indeed, micromolar ABA stimulated insulin release in vitro, from rat insulinoma cells and from isolated human islets [ 12 ], and also in vivo, in the perfused rat pancreas [ 13 ]. In the in vitro study, the role of cADPR as the second messenger of ABA was confirmed, similarly to what observed on innate immune cells.…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews address possible applications of ABA as a nutraceutical or pharmaceutical [2527] and several patents have been filed in this regard (see [28, 29] for examples). Effects of ABA include stimulating insulin secretion [30, 31] and anti-inflammatory responses [32] as well as reducing the severity of malaria disease [33].…”
Section: Introductionmentioning
confidence: 99%